Childhood Emotional Neglect and Adolescent Depression: Assessing the Protective Role of Peer Social Support in a Longitudinal Birth Cohort - Glickman, Emma A.; Choi, Karmel W.; Lussier, Alexandre A.; Smith, Brooke J.; Dunn, Erin C. (Frontiers in Psychiatry, 2021)
Introduction: Childhood adversities have been shown to increase psychopathology risk, including depression. However, the specific impact of childhood emotional neglect on later depression has been understudied. Moreover, few studies have investigated relational protective factors that may offset the risk of depression for children that experienced emotional neglect. Analyzing data (n=3,265) from the Avon Longitudinal Study of Parents and Children (ALSPAC) study, a longitudinal birth cohort of children born to pregnant women residing in Avon, UK from 1990-1992, we assessed the prospective relationship between childhood emotional neglect and depressive symptoms in late adolescence, and tested whether peer social support in mid-adolescence moderates this relationship. Methods: Childhood emotional neglect, defined as the absence of parental attention and support, was measured across seven assessments from age 8 to 17.5. Peer social support was measured at age 15. Depressive symptoms were measured at age 18. We analyzed the associations between emotional neglect and depressive symptoms, and between peer support and depressive symptoms, and also tested interactive effects of peer support on the association between emotional neglect and depressive symptoms. Results: Higher levels of emotional neglect were associated with increased depressive symptoms at 18. Conversely, strong peer social support was associated with reduced depressive symptoms, though no significant interaction with emotional neglect was detected. Conclusion: Although childhood emotional neglect is a risk factor for later depression, our results suggest that strong peer social support at age 15 may generally reduce the risk of depressive symptoms by the time children reach late adolescence. Fostering strong peer support in youth may help offset depression risk for all youth, even among those who have experienced emotional neglect.